Performance Analysis of CuO/MoS2/SnS2 Multilayer Broadband Photodetector - Dwivedi A.K.; Agarwal L.; Jit S.; Tripathi S. (My University, 2025)
This letter proposes a low-cost Al/tin disulfide (SnS2)/molybdenum disulfide (MoS2)/cupric oxide (CuO), poly(3, 4-ethylene dioxythiophene) polystyrene sulfonate (PEDOT:PSS)/indium tin oxide (ITO) hybrid heterojunction fabricated on an ITO-coated polyethylene terephthalate (ductile PET) substrate using the low-cost sol-gel method. The proposed heterojunction shows a broadband photodetection. In the device, SnS2 serves as the electron transport layer and PEDOT:PSS as the hole transport layer. At the CuO/MoS2 heterojunction's depletion area, the significant band offset between CuO and MoS2 produces an effective built-in electric field that promotes photogenerated carriers' drifting and raises the photocurrent of the proposed photodetector. At -2-V bias and 0.118-μW illumination, the proposed device showed a broad photoresponse with the maximum responsivity, detectivity, external quantum efficiency (EQE), and the sensitivity of 150 A/W, 1.56 × 1012 Jones, 5.6 × 104%, and 5.44 at 350 nm; 185 A/W, 1.92 × 1012 Jones, 4 × 105%, and 13.80 at 600 nm; and 36 A/W, 4.5 × 1011 Jones, 1.5 × 105%, and 4.54 at 1050 nm, respectively. The trap-assisted photomultiplication phenomenon caused by defects in the active layers of photodetector is responsible for the high responsivity and EQE exceeding 100%. © 2017 IEEE.